Optimized preparation and characterization of CLEA-lipase from cocoa pod husk - Khanahmadi, Soofia; Yusof, Faridah; Amid, Azura; Mahat, Mohd Khairizal (Elsevier, 2014)
Cross-linked enzyme aggregate (CLEA), a new method of carrier free enzyme immobilization has many advantages and considered as an economical method in the context of industrial biocatalysis. In this research, a highly active and stable CLEA-lipase has been successfully prepared from cocoa pod husk (CPH), a by-product of the cocoa industry. Based on the Face Centered Central Composite Design (FCCCD) under Response Surface Methodology (RSM) using three important parameters, the optimal preparation condition of CLEA-lipase shows that the highest activity achieved is 9.407Uor 83% of the activity of the free lipase. It was prepared using 20% saturated (NH4)2SO4 as the precipitant, 60mMglutaraldehyde as the cross-linker and 0.169mM BSA as the feeder. The optimal reaction temperature and pH for both CLEA-lipase and free lipase differed, where they were 60 ◦C and 8.2 and 45 ◦C and 8 respectively. A systematic study of temperature and pH stability showed that CLEA-lipase is more stable than free lipase. Results also show that the prepared CLEA-lipase retained more than 50% of the initial activity after five repeated runs. The observed high stability and recyclability of CLEA-lipase prepared from CPH demonstrated that it has potential to be used in different industrial applications.